PEMANFAATAN DAN PENGEMBANGAN DANA ZAKAT PRODUKTIF DALAM PERTUMBUHAN EKONOMI MASYARAKAT DI TANJUNG SEBAOK KOTA TANJUNGPINANG - Mohamad Tedy Rahardi; Raja Hesti Hafriza (STAIN Sultan Abdurrahman Kepulauan Riau, 2019)
Etymologically Zakat has two meanings, namely increase and purification. Zakat in terminology is a predetermined measure of the obligatory assets of zakat which are distributed to eight groups of recipients of zakat on certain conditions. Zakat has a very strategic role in efforts to reduce poverty or economic development. In contrast to other sources of finance for development, zakat does not have any backlash except for the approval and expect merit from Allah alone. However, it does not mean the mechanism of zakat does not have a control system. Zakat can function as a source of socio-economic funds for Muslims. This means that the utilization of zakat which is managed by the Amil Zakat Agency is not only limited to certain activities that are based on conventional orientation, but can also be utilized for economic activities of the people, such as in poverty eradication programs and unemployment by giving zakat productive to those who need it as venture capital. This is a qualitative descriptive study. Data collection techniques used by the authors in this study are as follows: Observation, Interview, Literature Study, Questionnaire. In conclusion, based on the results of the questionnaire that the authors spread to respondents, and the data has been analyzed by researchers, which have tested the validity and reliability of the instrument, it can be concluded that the variable use of productive zakat funds examined in this study has a high influence on increasing community economy